مدى جواز أخذ العِوض مقابل الضمان دراسة أصولية تحليلية لقرارات المجلس الشرعي في البنك المركزي الماليزي: Permissibility of Charging Fees against Guarantee Fundamental and Analytical Study of Resolutions of (SAC-BNM) - Mowaffak Noureddin; Azman Bin Mohd. Noor; Arif Ali Arif (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص يدرس هذا البحث مسألة جواز أخذ العوض مقابل الضمان -الكفالة بالأجرة-، ويحلِّلُها من المنظور الفقهي والأصولي، كونها تعتبر واحدة من المسائل الهامّة في حقل التمويل الإسلامي، وقد تمّت دراسة المسألة في ضوء القرارات التي اتخذها المجلس الشرعي في البنك المركزي الماليزي (SAC-BNM) بهذا الخصوص. واتبع الباحث المنهج الوصفي من خلال الدراسة الوصفية للمسائل ذات الصلة، والمنهج التحليلي من خلال تحليل تلك المسائل ومناقشتها ونقدها وتقويمها، وكان مما توصّل إليه الباحث إنّ عدم وجود نصوص من القرآن والحديث، لا يعني إمكانية الاستناد إلى دليلي المصلحة والقياس في جواز أخذ العوض مقابل الضمان، وإن المؤسسات الضامنة إذا أدّت الدين عن الجهات المضمونة، ينبغي لها أن تطالِب تلك الجهات بمقدار ما أدت عنها من دين فقط، وتقتصر مصلحة المؤسسات الضامنة على ما اكتسبته من أجور مقابل أعمالها الحقيقة. Abstract This research studies the permissibility of guarantee with fees (kafalah bi al-ujrah) and analyzes it from the perspective of Fiqh and Usul Al-Fiqh, as it is considered one of the important issues in the field of Islamic finance. The issue has been studied in light of the resolutions adopted by the Shari’ah Advisory Council, Bank Negara Malaysia (SAC-BNM) in this regard. The researcher used the descriptive research method on descriptive related studies to describe the issue, while the analytical method was used in analyzing the issue, critically discussing it, and providing solutions to it. Among the findings of this research are: The absence of Qur’anic verses and Prophetic hadiths that forbid the issue does not mean the ability to rely on the two resources i.e., interest and analogy (qiyas, Maṣlaḥah) in the permissibility of charging fees without restrictions. The guarantee corporations should only demand the amount of the debt they have paid on behalf of the borrowers. The guarantee corporations are not allowed to charge any additional amount more than their actual expenses.